PROSEDUR PEMBAYARAN BELANJA ALAT LISTRIK JCH DAN SPI PADA DINAS PPKUKM DKI JAKARTA - Adelia Eka Putri Damayanti, (2022)
The development of globalization and government reforms which are followed by openness provide a demand for the Indonesian people to be able to compete with other countries and the emergence of aspects of accountability and transparency in the management of state and regional budgets. The presence of these demands has the effect of delegating central government affairs to local governments, known as regional autonomy. Regional autonomy gives local governments the freedom to manage their local revenue sources. In managing the regional budget, the regional government is guided by a document called the APBD. One of the components in the APBD is regional spending. Regional expenditure is a transaction of spending money carried out by local governments. This regional expenditure is also one of the activities carried out by the Dinas PPKUKM DKI Jakarta. The existence of JCH management carried out by the SME Sector at the Dinas PPKUKM DKI Jakarta, has led to transactions for purchasing electrical equipment to support JCH operational activities. In making payments for goods and services, the Dinas PPKUKM DKI Jakarta has 2 systems, namely SIPKD and CMS, as well as through 2 mechanisms, namely Money Supply mechanism and Direct mechanism.